CULTURAL LIFE IN THE BUKHARA EMIRATE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the cultural life of the Bukhara Emirate. In the 19th and early 20th centuries, this region was one of the major centers of science, architecture, literature, and art. The research findings indicate that madrasas and mosques played a crucial role as educational and religious centers, literature and art flourished, and traditional crafts enriched the cultural heritage of the people. Additionally, the maqom music and theater traditions were an integral part of the cultural environment. This article is dedicated to studying the cultural heritage of the Bukhara Emirate and its influence up to the present day.